Effects of Histoplasma capsulatum infection on activation and proliferation of hematopoietic stem cells (2022)
ABSTRACT: Hematopoietic stem cells (HSCs) are considered a multipotent population with high proliferative potential, and are widely used in the treatment of leukemias, multiple myeloma, and some lymphomas. In the context of infectious diseases, some microorganisms have been reported to induce changes in the expression of surface markers in HSCs by a direct effect or through the induction of cytokines. Systemic infections are characterized by inducing stress on the bone marrow, which is reflected in an increase or decrease in leukocytes and platelets in peripheral blood, a process known as ‘emergency hematopoiesis’. Histoplasmosis is a systemic mycosis caused by Histoplasma spp., which occurs mainly in immunosuppressed individuals; this mycosis can present a severe clinical picture with dissemination to various organs, including the bone marrow, and is associated with anemia and pancytopenia. So far, the effect of a possible interaction of Histoplasma with HSCs is unknown.